DYNAMIC SCORING OF TAX REFORMS IN THE EUROPEAN UNION. (26th November 2018) - Barrios, Salvador; Dolls, Mathias; Maftei, Anamaria; Peichl, Andreas; Riscado, Sara; Varga, Janos; Wittneben, Christian
Abstract: In this paper, we present the first dynamic scoring exercise linking a microsimulation and a dynamic general equilibrium model for Europe. We illustrate our novel methodology analyzing hypothetical reforms of the social insurance contributions system in Belgium. Our approach takes into account the feedback effects resulting from adjustments and behavioral responses in the labor market and the economy‐wide reaction to the tax policy changes essential for a comprehensive evaluation of the reforms. We find that the self‐financing effect of a reduction in employers' social insurance contribution is substantially larger than that of a comparable reduction in employees' social insurance contributions.